Successful transduction with AAV vectors after selective depletion of anti-AAV antibodies by immunoadsorption - Orlowski, Alejandro (2020)
Gene therapy with adeno-associated virus (AAV)-based vectors shows great promise for the gene therapeutic treatment of a broad array of diseases. In fact, the treatment of genetic diseases with AAV vectors is currently the only in vivo gene therapy approach that is approved by the US Food and Drug Administration (FDA). Unfortunately, pre-existing antibodies against AAV severely limit the patient population that can potentially benefit from AAV gene therapy, especially if the vector is delivered by intravenous injection. Here, we demonstrate that we can selectively deplete antiAAV antibodies by hemapheresis combined with AAV9 particles coupled to Sepharose beads. In rats that underwent hemapheresis and immunoadsorption, luciferase expression was dramatically increased in the hearts and fully restored in the livers of these rats. Importantly, our method can be readily adapted for the use in clinical AAV gene therapy.